(3hLgI fXQ eYGUQIs - (3YHO GdSdGe(B, (3CHhbMas ((3GdbGgQI(B:s (3eWHYI GdGTYGY(B,s, 2002)
(3JLO aj gPG GdcJGH (B: (3GdJWhjQ hGdCgejI GdfSHjI , WHjYI GdfTGW GdJShjbj , GdHjFI GdJShjbjI ,OQGSGJ Sdhc GdeSJgdc GdbWGYGJ GdShbjI EOGQI GdfTGW GdJShjbj , GJNGP hJNWjW hJfXje GdfTGW GdJShjb EQTGOGJ YGeI dQLd GdJShjb , GdehVhYGJ GdeYGUQI aj GdJShjbs
Keywords: (3EOGQI GdJShjbs